Allowing for household preferences in emission trading-A contribution to the climate policy debate - Michael Ahlheim; Friedrich Schneider (Johannes Kepler University of Linz, Department of Economics, 2000)
In the context of emission trading it seems to be taken as given that people's preferences can be ignored with respect to the whole process of fixing emission targets and allocating emission permits to polluters. With this paper we want to reopen the debate on how citizens can be involved in this process. We try to show how citizen preferences can be included in the process of pollution control through emission trading. We propose an emission trading system where all emission permits are initially allocated to households who are then allowed to sell them in the permit market or to withhold (at least some of) them in order to reduce total pollution. This proposal tries to overcome the fundamental disadvantage of traditional permit systems which neglect consumer preferences by solely distributing emission permits to producers / polluters. In our system the property right to nature is re-allocated to the households who obtain the opportunity of reducing actual emissions according to their personal preferences by withholding a part or all of the emission permits allotted to them. Such a change in environmental policy would mark a return to the traditional principles of consumer sovereignty by involving households (at least partially) in the social abatement decision process instead of excluding them. Another advantage of admitting households to the TEP market as sellers or buyers of permits is that this increases the number of agents in the permit market and thus significantly reduces the possibilities of strategic market manipulations.
Keywords: Q28; Q38; D18; 330; Environmental policy; tradable emission permits; climate policy; consumer sovereignty; Emissionsrechte; Privater Haushalt; Verbraucher; Theorie